1996
DOI: 10.1097/00006123-199605000-00042
|View full text |Cite
|
Sign up to set email alerts
|

Intra-aortic Balloon Pump Counterpulsation in the Management of Concomitant Cerebral Vasospasm and Cardiac Failure after Subarachnoid Hemorrhage: Technical Case Report

Abstract: We report two patients who had symptomatic cerebral vasospasm and cardiac failure after aneurysmal subarachnoid hemorrhage and who were treated successfully with intra-aortic balloon pump counterpulsation therapy. Both patients developed congestive heart failure and pulmonary edema while receiving postoperative hypertensive, hypervolemic, hemodilutional (Triple-H) therapy for symptomatic cerebral vasospasm. Both cases of cardiac failure were refractory to maximum pressor and inotropic infusions. Intra-aortic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…To our knowledge, IABP has been used before in only six patients with SAH to increase cerebral perfusion pressure in the setting of vasospasm [25,[38][39][40] ( Table 2). The ability of IABP counterpulsation to improve cerebral perfusion pressure in human subjects was reported by Nussbaum et al [38] in a patient suffering from SAH and myocardial infarction secondary to triple-H therapy for vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, IABP has been used before in only six patients with SAH to increase cerebral perfusion pressure in the setting of vasospasm [25,[38][39][40] ( Table 2). The ability of IABP counterpulsation to improve cerebral perfusion pressure in human subjects was reported by Nussbaum et al [38] in a patient suffering from SAH and myocardial infarction secondary to triple-H therapy for vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…PTA and stenting of the carotid artery is perceived to be a good alternative to vascular surgery in the presence of multiple comorbid conditions especially when performed by a well experienced operator [4]. Nevertheless, the complications and risks of the procedure should be noted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Apostolides et al [4] reported successful treatment using IABP therapy in two patients with concomitant cerebral vasospasm and cardiac failure after subarachnoid hemorrhage, illustrating the potential usefulness of IABP as an adjunctive treatment in patients with cerebrovascular insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The intra-aortic balloon pump has been successfully used to treat patients with symptomatic vasospasm who cannot tolerate or are refractory to ‘triple-H' therapy [129,130,131,132]. In 1 patient, CBF improvement ranging from 33 to 161% (average: 69.3%) above the baseline could be documented by serial measurements on xenon-enhanced CT [130].…”
Section: Novel and Alternative Therapies For Sah-induced Cerebral Vasmentioning
confidence: 99%